Genetic evaluation of the probability of pregnancy at 14 months for Nellore heifers - Eler, J. P.; Vander Silva, J. A.; Ferraz, JBS; Dias, F.; Oliveira, H. N.; Evans, J. L.; Golden, B. L. (Amer Soc Animal Science, 2002)
To estimate the heritability for the probability that yearling heifers would become pregnant, we analyzed the records of 11,487 Nellore animals that participated in breeding seasons at three farms in the Brazilian states of São Paulo and Mato Grosso do Sul. All heifers were exposed to a bull at the age of about 14 mo. The probability of pregnancy was analyzed as a categorical trait, with a value of 1 (success) assigned to heifers that were diagnosed pregnant by rectal palpation about 60 d after the end of the breeding season of 90 d and a value of 0 (failure) assigned to those that were not pregnant at that time. The estimate of heritability, obtained by Method 9, was 0.57 with standard error of 0.01. The EPD was predicted using a maximum a posteriori threshold method and was expressed as deviations from 50% probability. The range in EPD was -24.50 to 24.55%, with a mean of 0.78% and a SD of 7.46%. We conclude that EPD for probability of pregnancy can be used to select heifers with a higher probability of being fertile. However, it is mainly recommended for the selection of bulls for the production of precocious daughters because the accuracy of prediction is higher for bulls, depending on their number of daughters.
Keywords: beef cattle; genetic parameters; heifers; pregnancy